ASSOCIATION OF NUTRITION AND OVERCROWDED ON THE RISK OF PULMONARY TUBERCULOSIS IN SAMOSIR DISTRICT NORTH SUMATERA - Sitanggang, Helpi; Siregar, Fazidah Aguslina; Nurmaini, Nurmaini (Poltekkes Kemenkes Medan, 2020)
Background: Pulmonary tuberculosis is an infection diseases that continues to increase morbidity and mortality in Indonesia. In 2017, the cases of pulmonary TB in Samosir District was 252 cases, with incidence rate a smear-positive of 126 per 100,000 population. Smear positive pulmonary tuberculosis potential to infect other people who living in the same environtment.   Materials and Methods: This study aims to determine the association of nutritional status and lighting withsmear positive pulmonary tuberculosis. Methods: A case-control study was conducted among 63 cases of smear-positive pulmonary tuberculosis and 63 controls without pulmonary tuberculosis. The cases were retrieved from the TB Registry at health centre in Samosir District. The cases were recruited from June 2018 to March 2019. Data was collected using a set of questionnaireby interview. Simple logistic regressionwas used to compute the crude odds ratio for the association of nutritional and lighting with smear-positive pulmonary tuberculosis.   Result: This study indicated that there was an association of poor nutrition status (OR = 4.280; 95% CI: 1.849, 9.906), and an overcrowded (OR = 5.084;95% CI: 1.852, 13,995) with the incidence of smear-positive pulmonary TB in Samosir District.   Conclusion: The conclusion of this study there was an association between poor nutritional status and an overcrowded with smear-positive pulmonary TB in Samosir District. Some interventions needed including strengthening health promotion and supplementary feeding to TB patient.